Influência de defeitos nas propriedades mecânicas de juntas soldadas por FSW da liga AA6013-T6 - Marconato, Eduardo Amado (2009)
In 1991, it was developed a solid state welding process called Friction Stir Welding - FSW, intended to increase the number of applications for the aluminum and its alloys. As every welding process the presence of defects should be avoided to not compromise the quality of the welded joint. Some typical defects originating from FSW process are found in some joints depending of the welding parameters. Thus, this study has the purpose to evaluate the quality of welded joints in 3 mm thick 6013-T6 friction stir welded joints in function of the obtained defects, using different welding parameters. The characterization was based on metallography by OM and SEM of the welded joints in order to analyze the obtained defects. The mechanical properties were evaluated by tensile, microhardness and fatigue tests.Welds joints were intentionally produced to contain inner defects in the weld nugget like tunnel shaped along the joint and lack of root penetration of the welding tool. All welded conditions, the microhardness profiles show a big drop in hardness when crossing from the HAZ zone into the center of each weld, while the tensile and fatigue tests showed a strong defects influence in the mechanical properties. The lack of penetration weld defect had the worst results of mechanical properties compared to tunneling defects, and the sound weld joint exhibited the best results of mechanical properties for all conditions investigated.